Meningkatkan Hasil Belajar Matematika Siswa Melalui Model Kooperatif Tipe Student Team Achievement Division (STAD) - Wiwik Andriani; Irmawaty Natsir (Musamus University, 2020)
This research is a Classroom Action Research which aims to improve mathematics learning outcomes of students of class VIII B of PGRI 1 Tamalate Makassar. The subjects of this study consisted of 35 students. Data collection techniques used are observation sheets and tests at the end of each cycle in accordance with the material being taught. From the results of the analysis in the first cycle obtained mathematical learning outcomes of students with an average score of 55.43 and a standard deviation of 18.95 of the ideal score achieved is 100. In the second cycle, improvements and additional actions from the previous cycle were held so that an increase student mathematics learning outcomes with an average score of 73.71 with a standard deviation of 14.71 of the ideal score achieved is 100. Based on the results of the analysis it can be concluded that the mathematics learning outcomes of students of class VIII B SMP PGRI 1 Tamalate Makassar experienced an increase after it was implemented teaching and learning process by applying cooperative learning type Student Team Achievement Division (STAD).